2022
DOI: 10.1002/alz.12880
|View full text |Cite
|
Sign up to set email alerts
|

Blood RNA transcripts reveal similar and differential alterations in fundamental cellular processes in Alzheimer's disease and other neurodegenerative diseases

Abstract: Background Dysfunctional processes in Alzheimer's disease and other neurodegenerative diseases lead to neural degeneration in the central and peripheral nervous system. Research demonstrates that neurodegeneration of any kind is a systemic disease that may even begin outside of the region vulnerable to the disease. Neurodegenerative diseases are defined by the vulnerabilities and pathology occurring in the regions affected. Method A random forest machine learning analysis on whole blood transcriptomes from six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 172 publications
0
16
0
Order By: Relevance
“…Indeed, the advantage of blood cell-based transcriptomes has also been described in an elegant integrative study aimed at identifying signatures of vulnerability across different neurodegenerative disorders. 42 This evidence supports the need for producing more large-scale omics datasets for ALS 17,54 , which at the moment are very limited and often include a reduced number of healthy controls. This represents a limitation that has to be kept in mind even in regards to this study, since the inter-individual variability characterizing omics experiments is a source of larger inconsistency within healthy controls groups than in patients, which still share the underlying traits of the disease considered.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Indeed, the advantage of blood cell-based transcriptomes has also been described in an elegant integrative study aimed at identifying signatures of vulnerability across different neurodegenerative disorders. 42 This evidence supports the need for producing more large-scale omics datasets for ALS 17,54 , which at the moment are very limited and often include a reduced number of healthy controls. This represents a limitation that has to be kept in mind even in regards to this study, since the inter-individual variability characterizing omics experiments is a source of larger inconsistency within healthy controls groups than in patients, which still share the underlying traits of the disease considered.…”
Section: Discussionmentioning
confidence: 54%
“…Such an approach is made possible by the development of novel mathematical and machine-learning tools that, together with the increased accessibility to deep-sequencing analysis, offer the possibility of integrating different layers of biological information with the final aim of identifying druggable targets, as well as diagnostic and prognostic markers for human diseases. 41,42,43 In order to apply this strategy to ALS, we performed the first integrative, machine-learning-based analysis of transcriptomic, epigenetic and genetic data obtained from human cultured MN, blood and post-…”
Section: Discussionmentioning
confidence: 99%
“…While we have presented an approach for curated gene expression analyses covering select studies in PD and other NDDs, there are two there are two resources (and approaches) that the readers will find considerably useful. The first one is the application of machine learning methods on GEO microarray datasets from blood samples (blood transcriptome) in NDDs (8). This elegant report revealed that perturbations in several cellular pathways (e.g., mitochondrial function, immune response, protein synthesis) were a shared feature in common NDDs (8).…”
Section: Additional Resourcesmentioning
confidence: 99%
“…The first one is the application of machine learning methods on GEO microarray datasets from blood samples (blood transcriptome) in NDDs (8). This elegant report revealed that perturbations in several cellular pathways (e.g., mitochondrial function, immune response, protein synthesis) were a shared feature in common NDDs (8). Adopting similar high-content analyses on the brainderived datasets, which we have compiled (Table S2) may unravel unique mechanistic findings in one disease or across NDDs.…”
Section: Additional Resourcesmentioning
confidence: 99%
See 1 more Smart Citation